Evidence for a magnocellular disadvantage in early-onset schizophrenic patients: a source analysis of the N80 visual-evoked component - Nunez, Daniel; Rauch, Johanna; Herwig, Kerstin; Rupp, André; Andermann, Martin; Weisbrod, Matthias; Resch, Franz; Oelkers-Ax, Rieke (Schizophrenia research, 2013)
Background - Visual impairments in schizophrenia have been suggested to be partly caused by early processing deficits of the magnocellular (M) pathway. This might include disturbed interactions between the M and parvocellular (P) pathways and especially impaired M priming, which can disturb highlighting of relevant information. Such disorders may result from neurodevelopmental irregularities, which are assumed to be substantially involved in schizophrenia. This study sought to test the hypothesis that M priming is impaired in schizophrenia. In order to elucidate this neurodevelopmental aspect, we investigated patients with different ages of schizophrenia onset. This provided a useful design to integrate visual information processing in a neurodevelopmental model of schizophrenia. - Method - Nine stimulus conditions were used to investigate the M- and P-pathways and their interaction in a pattern reversal VEP paradigm. N80 generators were analyzed using source localization (Brain Electrical Source Analysis software: BESA). Forty schizophrenia patients (early-onset=19; adult-onset=21) were compared with age- and gender-matched healthy controls (early-onset controls=19; adult-onset controls=21). Hypotheses were tested using a bootstrap resampling procedure. - Results - The N80 component was represented by a single dipole located in the occipital visual cortex. The bootstrap analysis yielded significant differences between early-onset schizophrenia patients and controls. We found lower amplitudes in response to mixed M-P conditions and normal amplitudes in response to isolated P- and M-biased stimulation. Concerning the latencies, significant differences were found between adult-onset subjects and their controls, with prolonged latencies for schizophrenia patients. - Conclusions - The early VEP component N80 evoked by mixed M-P conditions is assumed to be a correlate of M priming and showed reduced amplitude in early-onset schizophrenic patients but not in adult-onset patients. These findings point towards an M priming deficit in early-onset patients and are compatible with a neurodevelopmental hypothesis of schizophrenia, probably reflecting asynchronies in brain maturational abnormalities occurring at different ages of illness onset.
Gesehen am 29.11.2021